Aconitase post-translational modification as a key in linkage between Krebs cycle, iron homeostasis, redox signaling, and metabolism of reactive oxygen species. (January 2014) - Lushchak, Oleh V.; Piroddi, Marta; Galli, Francesco; Lushchak, Volodymyr I.
Abstract : Aconitase, an enzyme possessing an iron–sulfur cluster that is sensitive to oxidation, is involved in the regulation of cellular metabolism. There are two isoenzymes of aconitase (Aco) – mitochondrial (mAco) and cytosolic (cAco) ones. The primary role of mAdco is believed to be to control cellular ATP production via regulation of intermediate flux in the Krebs cycle. The cytosolic Aco in its reduced form operates as an enzyme, whereas in the oxidized form it is involved in the control of iron homeostasis as iron regulatory protein 1 (IRP1). Reactive oxygen species (ROS) play a central role in regulation of Aco functions. Catalytic Aco activity is regulated by reversible oxidation of [4Fe-4S] 2+ cluster and cysteine residues, so redox-dependent posttranslational modifications (PTMs) have gained increasing consideration as regards possible regulatory effects. These include modifications of cysteine residues by oxidation, nitrosylation and thiolation, as well as Tyr nitration and oxidation of Lys residues to carbonyls. Redox-independent PTMs such as phosphorylation and transamination also have been described. In the presence of a sustained ROS flux, redox-dependent PTMs may lead to enzyme damage and cell stress by impaired energy and iron metabolism. Aconitase has been identified as a protein that undergoes oxidative modification and inactivation in aging and certain oxidative stress-related disorders. Here we describe possible mechanisms of involvement of the two aconitase isoforms, cAco and mAco, in the control of cell metabolism and iron homeostasis, balancing the regulatory, and damaging effects of ROS.